What network simulator questions do users ask? a large-scale study of stack overflow posts - Syful Islam; Yusuf Sulistyo Nugroho; Md. Javed Hoss (Institute of Advanced Engineering and Science, 2021)
The use of network simulator as a modern tool in analyzing and predicting the behaviour of computer networks has grown to reduce the complexity of its accuracy measurement. This growth of network simulator implementation have attracted the researchers and practitioners to share problems and discuss to improve the features. To communicate the issues relates to network simulators, users move to an online discussion platform, such as Stack Overflow. Although recent studies have shown the popularity and benefits of adopting network simulation tools, however, the challenges of using network simulator that users face remain mostly unknown. Therefore, in this paper, we examine 2,322 network-simulator-related Stack Overflow posts to provide insights on the topics that users are interested and the challenges they face. We apply the Latent Dirichlet Allocation topic modeling to understand the topics that are being discussed in Stack Overflow. Then, we investigate the popularity and difficulty of each topic. The results of this study show that users use Stack Overflow as an implementation guideline for network simulation model. We determine 8 discussion topics that are merged into 5 major categories. Most of the posts discuss simulation model configuration. We also observe that target network protocol modification and network simulator installation are the most popular topics among the users compared to other topics. Users are specially facing challenges on network simulator installation and target network protocol modification issues.